Konstitusionalitas Penunjukan Penjabat Kepala Daerah Dalam Perspektif Pasal 18 Ayat (4) UUD NRI 1945 - Yahuda, Efron Lasa; Michael, Tomy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The appointment of Acting regional heads has become a public spotlight, especially regarding legal issues concerning the constitutional validity of the Acting Head. This problem is closely related to the interpretation of Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. In this context, the mechanism for appointing Acting regional heads is not explicitly outlined in the 1945 Constitution of the Republic of Indonesia. In response, the central government through the Ministry of Home Affairs issued Permendagri No. 4/2023 to provide normative clarity regarding the appointment process. The vacancy of the regional head position was triggered by the implementation of the national simultaneous voting planned for November 2024, which caused the simultaneous voting in 2022 and 2023 to be canceled. This study aims to evaluate whether the appointment of Acting regional heads as regulated in Article 201 paragraph (9) of Law No. 6/2020 is in line with the mandate of Article 18 paragraph (4) of the 1945 NRI Constitution. By using the normative legal research method, law is viewed as a structure of norms that includes principles, rules, legislation, court decisions, and legal doctrine. The results of the study show that, textually and legally formal, the regulation of the appointment of Acting regional heads is in accordance with Article 201 of Law No. 6/2020. However, in terms of substance and material, this mechanism violates the principles of constitutionality, the rule of law, democracy, and regional autonomy as mandated by the 1945 NRI Constitution.